Charlie ‘unwrapped’: a scientific investigation of a mummified votive offering in the Australian Institute of Archaeology collection - Raymond, Carla A.; Bevitt, Joseph J. (Buried History: The Journal of the Australian Institute of Archaeology, 2019)
The research undertaken on the mummified animal (IA1.2402) to establish its authenticity, identity, age and provenance is described. A combination of established and novel non-destructive imaging techniques, including X-ray computed tomography (CT) and neutron computed tomography (NCT) made possible a detailed study of the mummy’s content, which was found to be a partial skeleton of a juvenile cat. Use of both techniques allowed for dual contrast and complementary study of bones, soft tissue, and textile components. NCT provided valuable insights into wrapping techniques used in the mummification process. Acquisition of radiocarbon dates provided quantitative results to compare with morphological observations and conclusions based on partiality of the contents. All techniques were employed to better define and profile the specimen within its historical, social and religious contexts, while causing as little physical disruption as possible.